2018
DOI: 10.1155/2018/1569029
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Production-Delivery Lot Sizing Model with Limited Production Capacity and Transportation Cost considering Overtime Work and Maintenance Time

Abstract: An extension of the integrated production-delivery lot sizing model with limited production capacity and transportation cost is investigated. We introduce the factor of overtime work into the model to improve the manufacturer’s production. In addition, when finishing a lot, the manufacturer has maintenance time to maintain and repair equipment for ensuring that the supply chain is operating continuously. By analyzing the integrated model, the solution procedure is provided to determine the optimal delivery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Lin et al [21] formulated a generalized integrated inventory model to investigate the production and delivery policies while incorporating transportation time and capacity utilization. Other related research about integrated inventory model also can be found in the studies of Shahpouri et al [22], Das et al [23], Zhang and Sun [12], and Zhou and Wang [24].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Lin et al [21] formulated a generalized integrated inventory model to investigate the production and delivery policies while incorporating transportation time and capacity utilization. Other related research about integrated inventory model also can be found in the studies of Shahpouri et al [22], Das et al [23], Zhang and Sun [12], and Zhou and Wang [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Step 6: for each chromosome b in population NewPop(iter + 1), calculate its probability prob b using equation (12). en, select some chromosomes having lower probability values in population NewPop(iter + 1) to form a new population NewPop1(iter + 1).…”
Section: Mixed Genetic Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Kangi et al [32] considered the problem of multiproduct production to meet external market demand with limited inventory. Zhang et al [33] studied the problem of mass production and delivery under limited production capacity and transportation conditions. Qing et al [34] studied the capacity allocation of suppliers under different channel structures (retail, direct sales, and dual-channel).…”
Section: Limited Productionmentioning
confidence: 99%